Contribution percentage of some physical variables And the skill of the players and its relationship to the results The teams qualified to the finals of the Cup World football in South Africa 2010 (Journal of the College of Basic Education, 2022)
The FIFA World Cup is one of the most important global events watched by all of the worldBeing the most popular and exciting, as well as the high capabilities and abilities that distinguish the playersThese teams and the birth of new stars who are distinguished by creative capabilities, so they are the focus of attention and interestSpecialists and academics in order to learn about the art of modern play and what it has reachedThe teams are of physical, skillful and tactical capabilities, being the elite and the best international football teams.The study aimed at identifying some of the physical and skill variables of the playersThe teams qualified for the World Cup, as well as knowing the nature of the relationship between these variablesAnd the percentage of their contribution to achieve their difference.